Pengaruh Atribut Toko dan Fashion Involvement terhadap Keputusan Pembelian Konsumen (Studi Kasus Pada Matahari Department Store Paragon Mall Semarang) - Puspa Budiani; Apriatni Endang Prihatini; Widiartanto Widiartanto (Universitas Diponegoro, 2015)
This research is motivated by the phenomenon of the rise of a variety of trade centers such as department stores, supermarkets, hypermart, etc. in Indonesia marks a change in consumer shopping behavior from traditional markets to modern market. Matahari Department Store is one of the largest department stores and always visited by most of people in Indonesia, because it has a good shop attributes. This study aimed to determine the effect of stores attribute and fashion involvement on consumer purchasing decisions in Matahari Department Store Paragon Mall Semarang.This type of research is explanatory research by data collection questionnaires. This study uses the 100 respondents who made a purchase at the Matahari Department Store Paragon Mall Semarang. The sampling technique of this study was accidental sampling and sampling is done through purposive sampling method. Test analysis tools used are validity and reliability testing. Analysis of the data used is the correlation coefficient, coefficient of determination, simple linear regression, t test, multiple linear regression, and F test.Based on the results of analysis show that in partial stores attribute contributed the influence on purchasing decisions by 15.3%, fashion variable involvement contributes influence on purchasing decisions by 43.5%. Simultaneously stores attribute and fashion involvement contributes influence on purchasing decisions by 43.6%.Conclusion this study shows attributes and fashion stores involvement partially and simultaneously influence consumer purchasing decisions in Matahari Department Store Paragon Mall Semarang. Based on these results, Matahari Department Store Paragon Mall Semarang should be able to maintain and continuously improve the attributes of existing stores, and fashion involvement of each consumer should be able to continue to influence the purchasing decisions of consumers, as well as the need for continued research by companies and others to determine the effect of variable other.